Photo-thermal-electric heating evaporator device and preparation method and application thereof

By constructing a sandwich structure photothermal-electrical evaporator with an electric heating layer and a photothermal gel layer on the surface of cotton fabric, the problem of insufficient performance of solar seawater desalination evaporators under low light conditions is solved, and efficient all-weather seawater desalination and stable water supply are achieved.

CN119660866AActive Publication Date: 2025-03-21DONGHUA UNIV

Patent Information

Application Number
CN202510136357.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-21
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

Existing solar seawater desalination evaporators have low evaporation rates under dark or low light conditions, and there are problems such as electrical energy loss, unstable electric heating performance, high voltage dependence and interface floating limitations.

Method used

The photothermal-electrical evaporator with a sandwich structure is used to construct an electric heat layer and a photothermal gel layer on the surface of the cotton fabric to realize the photothermal-electrical energy conversion, and combine the suspended evaporation mode to improve water supply capacity and salt removal resistance.

Benefits of technology

It achieves efficient all-weather desalination, reduces energy loss, improves the stability and water supply capacity of the evaporator, and overcomes the insufficient performance of traditional evaporators under low-light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660866A_ABST
    Figure CN119660866A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of seawater desalination, and particularly relates to a photo-thermal-electric heating evaporator device and a preparation method and application thereof.The preparation method comprises the following steps that S1, boron nitride is added into epoxy resin and stirred to form a mixed solution, the surface of stainless steel wire cloth is coated with the mixed solution and dried, the coating and drying processes are repeated for multiple times, and an electric heating layer is obtained; and S2, a cotton fabric and the electric heating layer obtained in the step S1 are stacked to form a middle layer, then photo-thermal hydrogel grows on the surfaces of the two sides of the middle layer, standing and freezing are conducted, and the photo-thermal-electric heating evaporator device is obtained. Compared with the prior art, the problems of electric energy loss, unstable electric heating performance, high voltage dependence and interface floating limitation of an evaporator in the prior art are solved. According to the scheme, the photo-thermal-electric heating evaporator of a sandwich structure is constructed, and the photo-thermal-electric heating evaporator has excellent photo-thermal-electric heating performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of seawater desalination, and in particular relates to a photothermal-electrothermal evaporation device and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry and the sharp increase in the global population, the total global water consumption continues to rise. By 2050, more than half of the world's population will face the dilemma of fresh water shortage. Seawater is one of the most abundant resources on earth, occupying more than 70% of the earth's surface. Using seawater desalination to produce fresh water is one of the effective ways to effectively alleviate the fresh water crisis. For this purpose, people have developed a variety of seawater desalination technologies, including seawater distillation, electrodialysis, reverse osmosis, etc. However, these methods require direct or indirect consumption of a large amount of fossil energy, increase costs and cause secondary environmental pollution.

[0003] As a green and sustainable energy source, solar energy has attracted widespread attention because its use in seawater evaporation can effectively reduce the consumption of traditional fossil energy. The core of solar desalination is to develop evaporators based on photothermal materials. Under strong light conditions, the evaporator absorbs light energy through photothermal materials and converts it into heat energy, which is then transferred to the surface of the material for evaporating seawater. However, most regions and times in the world are in darkness or low light conditions, resulting in unsatisfactory evaporation performance of most evaporators. Therefore, it is urgent to develop a new type of solar evaporator to achieve all-weather seawater desalination to obtain fresh water.

[0004] Faced with the problem of low evaporation rate of traditional evaporators under dark or weak light conditions, coupled electrothermal conversion technology is considered to be an effective strategy to solve this problem. Its core is to develop high-conductivity photothermal material evaporators (such as graphene oxide aerogel, carbon nanotube aerogel, Mxene aerogel, metal-based materials and carbon fiber cloth, etc.) or photothermal material coupled conductive material evaporators (such as aerogel / copper sheet, carbon fiber / stainless steel wire, etc.). However, these evaporators still have the following problems: (1) During the power-on process, electrons will come into direct contact with seawater, resulting in power loss and unstable electrothermal performance; (2) A higher voltage is required for electrothermal evaporation, showing high voltage dependence; (3) The evaporation mode is limited to interface floating, with defects such as insufficient water supply and weak anti-salting ability. Summary of the invention

[0005] The purpose of the present invention is to provide a photothermal-electrothermal evaporation device and its preparation method and application in order to solve at least one of the above problems, so as to solve the problems of the evaporator in the prior art: power loss, unstable electrothermal performance, high voltage dependence, and limitation to interface floating. This scheme constructs a sandwich-structured photothermal-electrothermal evaporator with excellent photothermal-electrothermal performance.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The first aspect of the present invention discloses a method for preparing a photothermal-electrothermal evaporation device, comprising the following steps:

[0008] S1: Adding boron nitride to epoxy resin and stirring to form a mixed solution, coating the mixed solution on the surface of the stainless steel wire cloth and drying, repeating the coating and drying process several times to obtain an electric heating layer;

[0009] S2: stacking the cotton fabric and the electric heating layer obtained in step S1 to form an intermediate layer (one electric heating layer is stacked on each side of the cotton fabric, i.e., an ABA structure), then growing a photothermal water gel on both sides of the intermediate layer, letting it stand and freezing it to obtain the photothermal-electrothermal evaporation device.

[0010] Preferably, in step S1, the boron nitride accounts for 10-60% of the total mass of the boron nitride and the epoxy resin, and the concentration of the epoxy resin in the boron nitride and the epoxy resin is 0.1-2 g / g.

[0011] Preferably, in step S1, the stainless steel wire cloth is subjected to ultrasonic pretreatment, and the ultrasonic pretreatment is performed in a solution of ethanol, water and acetone in equal volume proportions.

[0012] Preferably, in step S1, the drying temperature is 40-100°C.

[0013] Preferably, in step S1, the coating and drying process is repeated 3 to 10 times.

[0014] Preferably, in step S2, the cotton fabric is subjected to ultrasonic pretreatment, and the ultrasonic pretreatment is carried out in a solution of ethanol, water and acetone in equal proportions.

[0015] Preferably, in step S2, the cotton fabric is cotton cloth.

[0016] Preferably, in step S2, the photothermal water gel is a hydrogel containing a photothermal material; the photothermal material is graphite, graphene, carbon nanotubes or graphene oxide, with a concentration of 0.01 to 0.5 g / L; the hydrogel is chitosan, polyvinyl alcohol, polyacrylic acid or polyethylene glycol, etc., with a concentration of 0.01 to 0.5 g / L; the photothermal water gel is obtained by uniformly mixing the photothermal material in a hydrogel solution and then freezing and cross-linking.

[0017] Preferably, in step S2, the standing time is 12 to 24 hours and the temperature is 20 to 30° C.; the freezing temperature is -60 to 0° C. and the time is 12 to 24 hours.

[0018] The second aspect of the present invention discloses a photothermal-electrothermal evaporation device, which is prepared by any of the preparation methods described above.

[0019] The third aspect of the present invention discloses an application of the above-mentioned photothermal-electrothermal evaporation device in seawater desalination.

[0020] Preferably, the photothermal-electrothermal evaporation device is applied to a light-oriented suspension device to evaporate seawater under light and power conditions, thereby achieving efficient and continuous production of fresh water around the clock.

[0021] The working principle of the present invention is:

[0022] This scheme uses cotton fabric as the substrate, and constructs an electric heating layer and a photothermal gel layer on its surface in sequence to jointly form a photothermal-electrothermal evaporation device. First, a layer of thermally conductive insulating material is attached to the surface of the stainless steel wire cloth by dip coating to prepare the electric heating layer, which can effectively transfer Joule heat and inhibit electrons from entering the water body, ensuring the excellent electric heating performance of the electric heating layer; then, with cotton fabric and the electric heating layer as the middle layer, the hydrogel containing the photothermal material is grown on the upper and lower surfaces of the middle layer by the freeze cross-linking method, thereby constructing a sandwich-structured photothermal-electrothermal evaporation device, giving it excellent photothermal-electrothermal performance. In addition, by combining the photothermal-electrothermal evaporation device with the hanging evaporation mode, the water supply capacity and anti-salting performance of the evaporator are improved, and efficient all-weather seawater desalination is achieved.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides a novel method for constructing a photothermal-electrothermal evaporation device, which has the characteristics of simple preparation, stable effect, and good mechanical properties;

[0025] (2) Water vapor can be generated from all surfaces of the hydrogel, increasing the area for steam generation and improving the efficiency of steam generation;

[0026] (3) Compared with the traditional all-weather evaporator, the electric heating layer in the present invention can quickly transfer the Joule heat, while avoiding direct contact between electrons and seawater, reducing energy loss;

[0027] (4) The present invention provides a light-oriented suspended all-weather evaporation device, which exhibits a high photothermal-electrical co-evaporation rate and provides a new idea for obtaining fresh water for seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the process of preparing a photothermal-electrothermal evaporation device;

[0029] Figure 2The actual photograph and scanning electron microscope image of the photothermal layer (a) and the electric heating layer (b) of Example 1;

[0030] Figure 3 The ultraviolet-visible-near infrared absorption spectrum of the photothermal layer of Example 1 (a) and the volt-ampere characteristic curve of the electric heating layer (b);

[0031] Figure 4 Schematic diagram of the photothermal suspension all-weather evaporation device of Example 1 (a) and the photothermal (b), electric thermal (c) and photothermal + electric thermal (d) evaporation performance tests. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0033] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are well known in the art.

[0034] A photothermal-electrothermal evaporation device is composed of cotton cloth, an insulating stainless steel wire cloth electric heating layer and a photothermal water gel, that is, the cotton cloth and the electric heating layer are used as the middle layer, and the photothermal water gel is constructed on the upper and lower surfaces to form a sandwich structure. The constructed photothermal-electrothermal evaporator can not only perform effective photothermal and electric thermal energy conversion, but also realize all-weather photothermal-electrothermal synergistic evaporation.

[0035] A method for preparing a photothermal-electrothermal evaporation device, comprising:

[0036] (1) First, add an appropriate amount of boron nitride to the epoxy resin solution and stir for 1 to 2 hours. Then, brush the mixed solution onto the pretreated stainless steel wire cloth, fully dip and dry it, and repeat the operation several times to obtain the electric heating layer.

[0037] (2) The above-mentioned electric heating layer and the pretreated cotton cloth are stacked together, and a hydrogel containing a photothermal material is grown on the upper and lower surfaces thereof. The hydrogel is allowed to stand and freeze for 12 to 24 hours to obtain a photothermal-electrothermal evaporation device.

[0038] In step (1), the mass fraction of boron nitride is 10% to 60%; and the concentration of epoxy resin is 0.1 to 2 g / g.

[0039] In step (2), the photothermal material is graphite, graphene, carbon nanotubes or graphene oxide, etc., with a concentration of 0.01 to 0.5 g / L; the hydrogel is chitosan, polyvinyl alcohol, polyacrylic acid or polyethylene glycol, etc., with a concentration of 0.01 to 0.5 g / L; the standing time is 12 to 24 hours, and the temperature is 20 to 30°C; the freezing temperature is -60 to 0°C.

[0040] An application of a photothermal-electrothermal evaporation device, specifically: an application of a phototropic suspension type interface evaporator based on a novel photothermal-electrothermal evaporation device, combining the novel photothermal-electrothermal evaporation device with a phototropic suspension evaporation device to construct a phototropic suspension type all-weather evaporator.

[0041] Example 1

[0042] The construction process of the new photothermal-electrothermal evaporation device is as follows Figure 1 shown.

[0043] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.075g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0044] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0045] Physical photos and scanning electron microscope images of the photothermal layer and the electrothermal layer:

[0046] As attached Figure 2 As shown, the photothermal layer hydrogel ( Figure 2 (a)) presents a lamellar porous structure, and graphite particles are evenly distributed on its surface; the electric heating layer ( Figure 2 (b)) shows that the surface of the stainless steel wire is uniformly covered with a layer of boron nitride / epoxy resin coating, proving the successful synthesis of the photothermal layer and the electrothermal layer.

[0047] The UV-visible-near infrared absorption spectrum of the photothermal layer and the volt-ampere characteristic curve of the electric heating layer:

[0048] The results are attached Figure 3 As shown, the CS / PDA@C photothermal gel layer ( Figure 3 (a)) can achieve a light absorption efficiency of 94%, and the electric heating layer ( Figure 3 (b)) exhibits good electrical conductivity.

[0049] Schematic diagram of the all-weather evaporation device with photothermal suspension and performance tests of photothermal, electric thermal, and photothermal + electric thermal evaporation:

[0050] The experimental device is as attached Figure 4 As shown in (a) (refer to the phototropic evaporation device in CN111348708A), the evaporation performance of the phototropic suspension all-weather evaporator was tested: under a simulated light intensity of one times (1.0 kW m -2 , i.e. 1sun, simulating sunlight) and / or 2V DC power supply, the two water tanks are placed horizontally, the cotton fabric of the new photothermal-electrothermal evaporation device is fixed between the two tanks with a magnet, the light source is irradiated on the photothermal layer, and the electrode clip of the power supply is connected to the electric heating layer. The room temperature is maintained during the test, and the whole device is placed on an electronic balance. The mass change of the whole device after different evaporation times is recorded, and the evaporation rate under different time conditions is calculated.

[0051] The results are attached Figure 4 (b), (c) and (d) show the mass loss of the new photothermal-electrothermal evaporation device in simulated seawater. The device has excellent photothermal, electrothermal and photothermal-electrothermal evaporation performance. Figure 4 In (b), 20, 40, and 300 mesh SEB+CPC represent 20 mesh SWWC / EP@BN+CS / PDA@C, 40 mesh SWWC / EP@BN+CS / PDA@C, and 300 mesh SWWC / EP@BN+CS / PDA@C, respectively, and the mesh represents the number of holes per unit area.

[0052] Example 2

[0053] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the amount of boron nitride added is 0.25 g. The specific steps are as follows:

[0054] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0055] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0056] Example 3

[0057] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the amount of boron nitride added is 0.05 g. The specific steps are as follows:

[0058] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.05g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0059] 2×8cm 2The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0060] Example 4

[0061] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the mixture is placed in an oven at 100°C for drying; and the operation is repeated 6 times. The specific steps are as follows:

[0062] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, and placed in a 100℃ oven for drying for 20min. The operation was repeated 6 times to obtain an electric heating layer (SWWC / EP@BN).

[0063] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0064] Example 5

[0065] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the steps are as follows: drying in a 40°C oven and repeating the operation 10 times:

[0066] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in a 40℃ oven and dried for 20min, and the operation was repeated 10 times to obtain the electric heating layer (SWWC / EP@BN).

[0067] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0068] Example 6

[0069] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the photothermal material is graphene and the hydrogel is polyvinyl alcohol. The specific steps are as follows:

[0070] 1.5×1.5cm 2The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0071] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphene (GN@PDA) was added to 5mL of 2% polyvinyl alcohol (PVA) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (PVA / PDA@GN) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+PVA / PDA@GN).

[0072] Example 7

[0073] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the photothermal material is carbon nanotubes and the hydrogel is polyethylene glycol. The specific steps are as follows:

[0074] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0075] 2×8cm 2The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of carbon nanotubes (CNT@PDA) modified with dopamine was added to 5mL of 2% polyethylene glycol (PEG) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (PEG / PDA@CNT) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+PEG / PDA@CNT).

[0076] Example 8

[0077] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the photothermal material is graphene oxide and the hydrogel is polyacrylic acid. The specific steps are as follows:

[0078] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0079] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphene oxide (GO@PDA) was added to 5mL of 2% polyacrylic acid (PAA) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (PAA / PDA@GO) was allowed to crosslink on both sides of the middle layer for 24h; then it was placed in a 0℃ refrigerator and frozen for 12h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+PAA / PDA@GO).

[0080] Example 9

[0081] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the cross-linking is allowed to stand at room temperature for 16 hours and then frozen at -60°C for 18 hours. The specific steps are as follows:

[0082] 1.5×1.5cm 2 The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0083] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 16h; then it was placed in a -60℃ refrigerator and frozen for 18h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0084] Example 10

[0085] The preparation steps of this embodiment are basically the same as those of embodiment 1, with the main difference being that the cross-linking is allowed to stand at room temperature for 12 hours and then frozen at -30°C for 24 hours. The specific steps are as follows:

[0086] 1.5×1.5cm 2The stainless steel wire cloth (SWWC) was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) for ultrasonic treatment for 40 minutes, and then washed and dried after the ultrasonic treatment. Then, 0.25g of boron nitride (BN) and 0.25g of epoxy resin (EP) were added to 0.5g of diluent (polypropylene glycol diglycidyl ether) respectively, and stirred for 1.5h to obtain a mixed solution. After 0.1g of curing agent (2-ethyl-4-methylimidazole) was added dropwise to the above mixed solution, it was evenly brushed on the pretreated stainless steel wire cloth, placed in an oven at 80℃ and dried for 20min, and the operation was repeated 3 times to obtain the electric heating layer (SWWC / EP@BN).

[0087] 2×8cm 2 The cotton cloth was placed in a mixed solution of anhydrous ethanol, acetone and deionized water (equal proportions) and ultrasonicated for 40 minutes. After the ultrasonication, it was washed and dried; then 0.05g of dopamine-modified graphite powder (C@PDA) was added to 5mL of 2% chitosan (CS) solution and stirred for 30min to obtain a mixed solution; 0.5mL of glutaraldehyde crosslinker solution was added dropwise to the mixed solution, and after stirring evenly, it was added to two molds with a volume of 2.5mL respectively; then the electric heating layer was placed in the middle position of the cotton cloth as the middle layer, and the two molds were buckled together from both sides of the middle layer, and the photothermal water gel (CS / PDA@C) was allowed to crosslink on both sides of the middle layer for 12h; then it was placed in a -30℃ refrigerator and frozen for 24h to obtain a photothermal-electrothermal evaporation device (SWWC / EP@BN+CS / PDA@C).

[0088] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a photothermal-electrothermal evaporation device, characterized in that: The steps include: S1: Adding boron nitride to epoxy resin and stirring to form a mixed solution, coating the mixed solution on the surface of the stainless steel wire cloth and drying, repeating the coating and drying process several times to obtain an electric heating layer; S2: stacking the cotton fabric and the electric heating layer obtained in step S1 to form an intermediate layer, then growing photothermal water gel on both sides of the intermediate layer, standing and freezing, to obtain the photothermal-electrical thermal evaporation device.

2. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S1, the boron nitride accounts for 10-60% of the total mass of the boron nitride and the epoxy resin, and the concentration of the epoxy resin in the boron nitride and the epoxy resin is 0.1-2 g / g.

3. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S1, the stainless steel wire cloth is subjected to ultrasonic pretreatment, and the ultrasonic pretreatment is performed in a solution of ethanol, water and acetone in equal proportions.

4. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S1, the drying temperature is 40-100°C.

5. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S1, the coating and drying process is repeated 3 to 10 times.

6. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S2, the cotton fabric is subjected to ultrasonic pretreatment, and the ultrasonic pretreatment is carried out in a solution of ethanol, water and acetone in equal proportions.

7. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S2, the photothermal water gel is a hydrogel containing a photothermal material; the photothermal material is graphite, graphene, carbon nanotubes or graphene oxide, with a concentration of 0.01 to 0.5 g / L; the hydrogel is chitosan, polyvinyl alcohol, polyacrylic acid or polyethylene glycol, with a concentration of 0.01 to 0.5 g / L.

8. The method for preparing a photothermal-electrothermal evaporation device according to claim 1, characterized in that: In step S2, the standing time is 12 to 24 hours at a temperature of 20 to 30°C; the freezing temperature is -60 to 0°C for 12 to 24 hours.

9. A photothermal-electrothermal evaporation device, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the photothermal-electrothermal evaporation device according to claim 9 in seawater desalination.

Citation Information

Patent Citations

  • Phototropic solar photo-thermal seawater evaporation method and phototropic solar photo-thermal seawater evaporation device

    CN111348708A

  • Light energy and electric energy composite energy element and preparation method thereof

    CN106245146A

  • Photo-thermal controllable multilayer liftable cultivation rack for wheat-maize seedling cultivation

    CN109168773A

  • Solar-driven photo-thermal-thermoelectric coupling synergistic interface evaporation device

    CN113294922A

  • Photo-thermal-electric-thermal synergistic corrugated paper interface evaporation desalting device and preparation method thereof

    CN115159608A

Cited By

  • Interface water evaporator and preparation method and application thereof

    CN121342125A

  • Interface water evaporator and preparation method and application thereof

    CN121342125B